2020
DOI: 10.1186/s12913-019-4861-z
|View full text |Cite
|
Sign up to set email alerts
|

Elder abuse in Norwegian nursing homes: a cross-sectional exploratory study

Abstract: Background: Elder abuse is a global public health and human rights problem that is predicted to increase as many countries experience a rapid growth in their population of older adults. Elder abuse undermines an older person's well-being and is associated with a range of serious health consequences. In institutional care settings, older residents are particularly vulnerable and hence at higher risk of being abused, but few countries have explored the extent and nature of this phenomenon in national studies. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(94 citation statements)
references
References 44 publications
(80 reference statements)
4
89
1
Order By: Relevance
“…Along with competent pain and symptom management, the nature of the nurse-patient interaction in long-term NH care is crucial. Frustration, suffering, hopelessness, meaninglessness and depression result from not being attended to or treated with indifference, and thereby violating individuals' sense of worthiness [113,114] which negatively impact residents' mental and physical symptoms or ailments [29,112]. Possibly, older adults' self-acceptance and thereby their sense of self-worth and value can be strengthened by active listening, recognizing and empowering the uniqueness of this person whose subjective experiences are taken seriously and respected, all of which supporting global wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Along with competent pain and symptom management, the nature of the nurse-patient interaction in long-term NH care is crucial. Frustration, suffering, hopelessness, meaninglessness and depression result from not being attended to or treated with indifference, and thereby violating individuals' sense of worthiness [113,114] which negatively impact residents' mental and physical symptoms or ailments [29,112]. Possibly, older adults' self-acceptance and thereby their sense of self-worth and value can be strengthened by active listening, recognizing and empowering the uniqueness of this person whose subjective experiences are taken seriously and respected, all of which supporting global wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…In this article we will present findings on resident-to-resident aggression. The prevalence of staffto-resident abuse is reported elsewhere [37].…”
Section: Methodsmentioning
confidence: 99%
“…The remaining 3693 participants were included in the analysis, giving an analytic response rate of 58.3%. The flowchart of randomisation and recruitment is shown in Botngård et al [37].…”
Section: Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaders of these institutions have a responsibility to ensure that residents' human rights are protected, and that residents are safe and free from harm [9,10]. However, research have found high rates of staff-to-resident abuse in nursing homes [11][12][13].…”
Section: Introductionmentioning
confidence: 99%